Inclusive & rehabilitative environment : the application of universal design principles to rehabilitate mainstream society's attitude toward disabilities & access - Bawa, Hiten M (School of Architecture, Planning and Geomatics, 2014)
This "Inclusive and Rehabilitative Environment" dissertation focuses on the application of Universal Design principles and changing attitudes toward people with disabilities in the built environment. The choice of research subject is partly influenced by my disability as a profoundly deaf person and as a bilateral cochlear implant user as well as from my exposure to the spatial challenges people with disabilities face in the built environment. Cape Town’s built environment was designed and constructed with no reference to the needs of people with disabilities and the ageing population (Davies, 2013; Thompson 2013). It continued to perpetuate the social and attitudinal barriers toward disabilities despite recent attempts and policies at improving accessibility (Daniels, 2013; Opperman, 2013, Mycroft, 2013). There are few buildings in Cape Town that are accessible but most of them are restricted to institutional typologies. In addition, the research focus is further motivated by the following points: * There is a lack of relevant and updated resources on Universal Design in South Africa compared to First World countries (Davies; 2013; Lehohla, 2005; Opperman, 2013; Thompson; 2013). * The recently updated section of the National Building Regulation SANS 10400, Part S: Facilities for persons with disabilities, is a significant advancement for the rights of people with disabilities. Granted, the legal frameworks, policies and guidelines are theoretically in place. They are seldom applied in practice and are often not enforced (Thompson, 2013). * There is a lack of understanding on applying accessibility features to suit the local context compared to international examples (Daniels, 2013; Davies; 2013).